Industrial Heritage as a Brand of the Ural Region in the Context of New Industrialization - Vladimir V. ZAPARIY; Ekaterina V. ZAITSEVA; Nаtаliа V. GONCHAROVA (Communications of International Proceedings, 2020)
The topic of the article is extremely relevant at the present time, because there is a need to create an economically attractive image of the Ural region.  In the article, the authors touch upon an unusual aspect that influences on the development of new industrialization in such an old industrial region as the Urals - the industrial legacy.  They put forward a hypothesis, which they argue that brands created on the basis of the industrial heritage of the region can have a significant impact on the development of the Ural region.  Through the creation of a special brand on the basis of industrial heritage, it is possible to promote products of the region, develop industrial tourism as one of the competitive products of the region, and gain a competitive advantage in modern economic connections. Arguments and proposals are made for such work by regional authorities and public organizations.
Keywords: Urals; Industrial Heritage; New Industrialization; Image; Brand.